Application of tactile/kinesthetic stimulation in preterm infants: a systematic review - Vanessa C. Pepino; Maria Aparecida Mezzacappa (Elsevier, 2015)
OBJECTIVE: To verify the methods used by the clinical trials that assessed the effect of tactile/kinesthetic stimulation on weight gain in preterm infants and highlight the similarities and differences among such studies. SOURCES: This review collected studies from two databases, PEDro and PubMed, in July of 2014, in addition to bibliographies. Two researchers assessed the relevant titles independently, and then chose which studies to read in full and include in this review by consensus. Clinical trials that studied tactile stimulation or massage therapy whether or not associated with kinesthetic stimulation of preterm infants; that assessed weight gain after the intervention; that had a control group and were composed in English, Portuguese, or Spanish were included. SUMMARY OF THE FINDINGS: A total of 520 titles were found and 108 were selected for manuscript reading. Repeated studies were excluded, resulting in 40 different studies. Of these, 31 met all the inclusion criteria. There were many differences in the application of tactile/kinesthetic stimulation techniques among studies, which hindered the accurate reproduction of the procedure. Also, many studies did not describe the adverse events that occurred during stimulation, the course of action taken when such events occurred, and their effect on the outcome. CONCLUSIONS: These studies made a relevant contribution towards indicating tactile/kinesthetic stimulation as a promising tool. Nevertheless, there was no standard for application among them. Future studies should raise the level of methodological rigor and describe the adverse events. This may permit other researchers to be more aware of expected outcomes, and a standard technique could be established.